A review of office buildings in Malaysia: the window and lighting designs - Denan, Zuraini; Mohd. Yaman, Maheran (Common Ground Publishing Pty Ltd, 2008)

(untitled)
This research reviews the background of office buildings in relation to their design development, window and lighting design and guidelines of office building design in Malaysia. It discusses the development of the office building, the design of workspace layout, the relevant window and lighting building regulation and the method and system of window shading.